Highly Nonlinear Solitary Wave Velocity Measurement with a Modified Michelson Interferometer - Labbe-Morales, R; Olivares-Bahamondes, I; Vergara-Cofre, L (Technical University of Wroclaw, 2017)
We have measured the velocity of a highly nonlinear solitary wave, generated by the collision of a ball with a linear set of pre-compressed balls of the same material, using a double Michelson interferometer. One of the mirrors of each interferometer was mounted on one of two balls of the array. The measured soliton velocity was u = (346 ± 40) m/s for brass balls with pre-compression force F = (0.8 ± 0.1) N, and u = (102 ± 3) m/s for Teflon balls with pre-compression force F = (0.4 ± 0.1) N.